Leadership Strategies to Achieve Organization with Superior Performance - David , David; Riyadi , Selamet; Lestari, Setyani Dwi; Saputro, Adi; Muhdaliha, Eryco (Maneggio, 2025)
Effective leadership strategies play a crucial role in achieving superior organizational performance. Leadership approaches such as transformational, visionary, and participative leadership contribute to enhancing productivity, efficiency, and overall organizational success. This study explores the relationship between leadership strategies and organizational performance, emphasizing how effective leadership can foster a positive work environment, drive employee motivation, and support strategic decision-making. Strong leadership is essential in navigating dynamic business challenges, ensuring adaptability, and promoting sustainable growth. The findings suggest that organizations should prioritize leadership development programs and adopt strategic leadership models to optimize performance. Additionally, fostering a culture of innovation, collaboration, and continuous improvement can further enhance organizational effectiveness. This study highlights the importance of leadership as a key factor in organizational success and provides insights into how leadership strategies can be effectively implemented to achieve long-term competitive advantage. Future research may explore additional factors influencing organizational performance, such as corporate culture and technological advancements.